Proposta de implantação do sistema de custos no Instituto Federal de São Paulo (IFSP) - Paula, Edmilson Antonio de (2024)
This study was developed with the general objective of identifying and demonstrating in practice what are the costs involved and the costs in square meters of public spaces occupied by the technical course in agriculture and livestocking at the Federal Institute of São Paulo (IFSP), to present a proposal on how to finance its developed activities and projects regarding the implementation of costs in the public institution of education, research and extension. Exploratory research and action research consists of a case study, due to being characterized mainly by the study concentrated on a single case study, which is preferred by researchers who wish to deepen their knowledge about a specific case, with documentary surveys for the appropriation of costs to the absorption costing method. In a practical way, this work guides campuses on how to finance their activities and projects. Therefore, it seeks to contribute to a costing system